Polymers dynamics of the nonfluoro, nano‐brush repelling agent with self‐stratifying property in water‐based coatings. Issue 39 (27th May 2019) - Tang, Wei‐Cheng; Su, Yi‐Che; Huang, Yun‐Shan; Yu, Ya‐Tin; Chen, Hsin‐Lung; Chu, I‐Ming
ABSTRACT: While perfluoroalkyl acids (PFAAs), also known as C8s, are used extensively in textile repellent coatings, concerns have arisen for their carcinogenicity and hazardous effects on the environment. In this study, a novel water‐based, nonfluoro, and nanobrush textile repelling agent was prepared by conventional sol–gel chemistry using amorphous fumed silica and n‐octyltriethoxysilane as the starting materials. Minimal interaction between the designed repelling agent and marketed water‐based resins was confirmed using linear viscosity region (LVR) analysis and asymmetric‐flow field‐flow fractionation (AF4), suggesting the self‐stratification potential of the repelling agent. More specifically, the repelling agent exhibited excellent compatibility and self‐stratifying ability with a force‐emulsified acrylic‐based resin, affording a water contact angle of 104.3° when incorporated at 7% solid content. Performance tests carried out on thermoplastic polyurethane (TPU) revealed excellent adhesion (100/100) of a final formulation, and a significant increase in water contact angle from 80.1° to 103.8° after treatment. In addition, the fouling area after the removal of a submerged sample from a mixture of slurry, polymer, and oil decreased from 48 to 1% when the repelling agent was added. Moreover, the sludge‐fouling property remained unchanged after 1000 cycles of abrasion. These findings demonstrate the potential of the described nonfluoro, nanobrush repelling agent as an environmentally safe alternative for use with commercial resins, in turn realizing a fully water‐based hydrophobic coating. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 48003. Abstract : The nonfluoro, nano‐brush repelling agent has self‐stratifying property in water‐based coatings.